Propostas de sequências didáticas para o ensino de funções pautadas na interdisciplinaridade e no uso das TDIC'S - Oliveira, Maria Edvanise (Universidade Federal Rural do Semi-Árido, 2021)
The present study was developed in the context of the social isolation caused by the pandemia of Covid-19, which had a great impact on the learning community with the insertion of remote teaching, demanding from the teacher a new way of teaching through Digital Information and Communication Technologies (ICTs). Influenced by this scenario and by a concern of building something useful to society, the research developed has as its main objective to present a compilation of activities related to function teaching, divided into five didactic sequences based on the interdisciplinarity and the use of ICTs. These sequences aim at increasing the interest and engagement of students in class, thus minimizing the existing difficulties in teaching function and providing meaningful learning. For this purpose, research was carried out on the teaching of functions both in the BNCC and ENEM matrices reference and SAEB, as they are documents that guide the development of the schools curriculum. Following that, a diagnosis of the difficulties in the teaching-learning process of function was carried out. Given the various difficulties presented, it was decided to adopt an interdisciplinary approach and the insertion of technological resources, as alternatives to minimize those difficulties and facilitate the understanding of the content in question. Among the range of technological resources available on the web, four tools were selected that are easy to access, free, practical and some already known by many high school teachers, those tools are: the digital platforms Youtube, Khan Academy, PhET and the GeoGebra Software. The elaboration of the activities present in the didactic sequences was based on proposals already applied by other teachers reported in academic works, as well as the study of the possibilities of application of the selected tools in the teaching of function. Thus, it is expected that the material presented here, in addition to contributing to a more significant learning of the concepts, contribute to a change in teachers' habits, as it presents possibilities of using the web as a reference for their lectures, in order to make them more dynamic and engaging. Finally, it is intended that the interdisciplinary approach and classes based on technological resources become something common in schools, as it can be adaptable to any subject or curricular component
Keywords: Funções; Sequência didática; Interdisciplinaridade; TDIC’s; Functions; Didactic/teaching sequence; Interdisciplinarity; ICTs; CIENCIAS EXATAS E DA TERRA::MATEMATICA